A comparative study of Educational Commonalities in Ibn al-Wardi's Lamiyah and Qaboos- Nameh: مشتركات تعليمى در لاميه ی ابن الوردى و قابوسنامه؛ بررسى مقايسه اى (Journal of the College of Languages (JCL), 2024)
A literary-educational work is a work that explains wisdom to the reader and presents moral, educational and instructional issues in a literary form. Qaboos-nameh or Nasihat al-Muluk is an educational and educational book that has a special place in the field of ethics and guidance, where the author guides his children. Also, Ibn al-Wardi's Lamiyah or Nasihat al-Akhwan is a poem containing moral advice and advice in 77 verses that Ibn al-Wardi wrote to his son.     It seems that the main goal of Ibn al-Wardi and Onsur AL-maali in Lamia and Qaboos-nameh was to express educational and moral issues and spread and convey them to future generations. Ibn al-Wardi, like Onsur AL-maali, listed moral points such as knowledge, humility, etc. among the good qualities and emphasized on them. Therefore, it seems that the educational views and moral points of Lamiyah and Qaboos-nameh are influenced by each other and in the same direction, and avoiding social and moral anomalies was one of the goals of these two authors. Moral positivity, avoiding abnormalities has also been intended.     This research with a descriptive-analytical method and after mentioning some points about the biographies of two poets; It examines some common moral doctrines and didactic points in these two works, and in addition to expressing the moral and didactic commonalities of the two works, the role of educational views and moral teachings of the two authors is examined to find out that How two writers have used the teachings based on their valuable experiences to expand educational and guidance matters.چکیده   اثر ادبی- تعلیمی، اثری است که حکمتی را برای خواننده تشریح میکند و مسایل اخلاقی، تعلیمی و ارشادی را به شکل ادبی عرصه کند. قابوسنامه یا نصیحت الملوک کتابی تعلیمی و تربیتی است که در حوزه اخلاق و ارشاد جایگاه ویژهای دارد که در آن نویسنده به ارشاد و راهنمایی فرزندش میپردازد. همچنین لامیة ابن الوردی یا نصیحة الاخوان منظومهای است مشتمل بر پندها و توصیههای اخلاقی در 77 بیت که ابن الوردی خطاب به فرزندش سروده است.     این پژوهش با روشی توصیفی- تحلیلی و پس از ذکر نکاتی در مورد زندگینامه دو شاعر؛ به بررسی برخی آموزههای اخلاقی و نکات تعلیمی مشترک در این دو اثر میپردازد و علاوه بر بیان مشترکات اخلاقی و تعلیمی دو اثر، نقش دیدگاههای تربیتی و آموزههای اخلاقی دو مولف بررسی میشود تا در یابد، این دو ادیب چگونه از آموزههای مبتنی بر تجربههای ارزشمند خود برای گسترش امور تعلیمی و ارشادی استفاده کردهاند. یافتههای پژوهش نشان میدهد که آموزههای اخلاقی و تربیتی نقش اساسی در اندیشههای این دو مولف دارند و آنها بر جهانی اخلاقی و مبتنی بر آموزههای اخلاق تاکید دارند؛ همچنین دلیل توفیق این دو مولف در پاسخ گویی به نیازهای اخلاقی و تربیتی، انتخاب موضوعات تعلیمی و ارشادی مهمی است که نقش اساسی در زندگی هر فردی دارند که از میان آنها میتوان به علم آموزی، افتخار نکردن به اصل و نسب، مرگ آگاهی و... اشاره کرد.Received on 4/7/2023  Accepted on 20/8/2023  Published on 2/1/2024